Evidence-based policy making: determining what is evidence - Phillips, Peter W.B. (Heliyon, 2020)
In the era of evidence-based policy, framing and assessing the core evidence is fundamental to our ability to use research in support of public policy. In a world of almost exponentially expanding scholarly publication, it is becoming harder to define what is known. This article reviews the basic theories of knowledge, the context for sorting through and summarizing that knowledge and a number of options available, and used, to assemble the knowledge base for research and policy work. The authors undertook a summative process in the domain of biotechnology, agriculture and development and offer insights into the comparative methods and their impacts on the outcome. A population sample of 421 articles was gathered. Four methods—expert Delphi, citation analysis, social network analysis and peer evaluation—were used to select the 51 pieces for inclusion and analysis in the core literature. That analysis shows that each process delivered a different set of evidence. The potential for bias in knowledge assessment can challenge policy makers in their process of reviewing evidence that rationalizes policy.